In-Vitro Evaluation of Antioxidant, Antiproliferative and Photo-Protective Activities of Benzimidazolehydrazone Derivatives - Anna Baldisserotto; Monica Demurtas; Ilaria Lampronti; Massimo Tacchini; Davide Moi; Gianfranco Balboni; Silvia Vertuani; Stefano Manfredini; Valentina Onnis (Pharmaceuticals, 2020)
In the search of multifunctional compounds we designed benzimidazole derivatives endowed with phenolic hydroxy groups and a hydrazone moiety as potential radical-scavenger and the antioxidant agents. The target molecules have been prepared by a simple synthetic procedure and tested for their antioxidant activity by DPPH, FRAP, and ORAC test, for photoprotective activity against UV rays and for antiproliferative activity against Colo-38 melanoma cells. Furthermore, two different dermocosmetic formulations were prepared with the compounds endowed with the best antioxidant and photoprotective profile and their release from formulation evaluated using Franz Cells system. High antioxidant activity is related to the presence of at least two hydroxy groups on arylidene moiety of benzimidazoles. Structure activity analysis revealed that the position of hydroxy groups is crucial for antioxidant activity as well as the presence of a 2-hydroxy-4-(diethylamino)arylidene group. The same correlation pattern was found to be related to photoprotective activity resulting in an UVA Protection Factor better than the commercial solar filter PBSA and antiproliferative activity against melanoma cells without producing cytotoxicity on normal keratinocytes. The release analysis indicated that high antioxidant activities are achieved with limited release at concentration compatible with the use as UV sunscreen filter.